Pemberdayaan Masyarakat Budidaya Asparagus Pada Kelompok Tani Renjani Di Banjar Selantang Desa Belok Sidan, Kecamatan Petang, Kabupaten Badung - Oktavianus Sumardana Pratama; I Made Sumada; Ni Made Anggia Paramesti Fajar (Public Inspiration : Jurnal Administrasi Publik, 2020)
This study aims to increase community empowerment to cultivate asparagus through the Asparagus Renjani Farmer Group, in Banjar Selantang, Belok Sidan Village, Petang District, Badung Regency, Bali. This research design uses a qualitative approach with descriptive analysis. The population in this study was the Asparagus Farmer Rinjani Group in Banjar Dinas Selantang, Belok Sidan Village, Petang District, which consisted of 18 members. This study uses data collection from primary and secondary sources with the technique of determining positive sampling of informants from the results of interviews with the chairman and members who are considered potential in providing relevant information and in accordance with the reality in the field. The results of the study are in accordance with the problems faced by the Asparagus Tani group. Renjani, the solution offered to Asparagus farmers and administrators of the Asparagus Tani Renjani group regarding the problem of seeding, as it has been explained that the seeds are imported from Taiwan. Farmers often complain that the seeds don't arrive at the targeted time, so the solution for that is that some farmers try to make their own seeds through seeds from the asparagus plant. Regarding financial management that has not been considered good, the solution we can provide is by educating on the importance of financial management and accounting. In carrying out promotions, it was conveyed to carry out promotions through social media. Given the development of increasingly sophisticated and practical and broad technology. Social media is a way that we can try to promote. Social media is broad and global.